2020
DOI: 10.1101/2020.06.17.153486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potent Neutralizing Antibodies Directed to Multiple Epitopes on SARS-CoV-2 Spike

Abstract: 23The SARS-CoV-2 pandemic rages on with devasting consequences on human lives and the 24 global economy. The discovery and development of virus-neutralizing monoclonal 25 antibodies could be one approach to treat or prevent infection by this novel coronavirus. 26Here we report the isolation of 61 SARS-CoV-2-neutralizing monoclonal antibodies from 5 27 infected patients hospitalized with severe disease. Among these are 19 antibodies that 28 potently neutralized the authentic SARS-CoV-2 in vitro, 9 of which exhi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
139
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(156 citation statements)
references
References 45 publications
17
139
0
Order By: Relevance
“…Most recent strategies to prevent SARS-CoV-2 entry into the host cell aim at blocking the ACE2-RBD interaction. High-affinity monoclonal antibodies, many identified from convalescent patients, are leading the way as potential therapeutics (22)(23)(24)(25)(26)(27)(28)(29). While highly effective in vitro, these agents are expensive to produce by mammalian cell expression and need to be intravenously administered by healthcare professionals (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recent strategies to prevent SARS-CoV-2 entry into the host cell aim at blocking the ACE2-RBD interaction. High-affinity monoclonal antibodies, many identified from convalescent patients, are leading the way as potential therapeutics (22)(23)(24)(25)(26)(27)(28)(29). While highly effective in vitro, these agents are expensive to produce by mammalian cell expression and need to be intravenously administered by healthcare professionals (30).…”
Section: Discussionmentioning
confidence: 99%
“…For one Class II nanobody, Nb3, we identified a likely binding site in the Spike S1 domain external to the RBDs. Previously discovered neutralizing antibodies from convalescent patients bind an epitope in a similar region of Spike (24,26,27). Binding of Nb3 to this epitope may allosterically stabilize RBDs in the down-state, thereby decreasing ACE2 binding.…”
Section: Discussionmentioning
confidence: 99%
“…to HIV-1 Env versus is binding to SARS-CoV-2 S is that on the HIV-1 Env all the binding glycans come from a single gp120 monomer in the HIV-1 Env trimer, whereas in the SARS-CoV-2 S protein the binding site is quaternary and the 2G12-binding glycans at each site are contributed by two of the three protomers, making this one of the first examples of a quaternary epitope spanning multiple protomers on the SARS-CoV-2 S protein (28), and the first in the S2 domain.…”
Section: Comparison Of 2g12 Binding To Sars-cov-2 Spike Versus Hiv-1 Envmentioning
confidence: 99%
“…Recent studies have shown that related, potently neutralizing monoclonal antibodies that recognize the SARS-CoV-2 receptor binding domain (RBD) are often elicited in SARS-CoV-2 infection (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). These antibodies have great potential to be clinically impactful in the treatment and prevention of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%